Effect of bubble volume on the sweeping velocity of air bubbles in horizontal pipelines in water supply system - Hu, Jianyong; Yang, Chengzhi; Zhang, Yuzhou; Song, Hongge; Lu, Miao; Meng, Zhenzhu; Zhang, Jinxin (Frontiers in Earth Science, 2023)
Trapped air bubbles in pipelines greatly affect the safety operation of water supply system. In some occasions, it may induce water hammer, and result to the explosion of pipelines and interruption of water supply system. Flushing the bubbles out of the pipeline before they form air pockets can effectively prevent the occurrence of pipeline explosion accidents. This paper give insights to the sweeping velocity of air bubbles in horizontal pipelines in water supply system. We first analyze the forces act on a single air bubble in a horizontal pipeline, and provide a theoretical expression for calculating the sweeping velocity of the air bubble. Physical model experiments are conducted with different parameters of air bubbles and pipelines. The variations of the sweeping velocity to the bubble volume and dimensionless bubble volume are determined experimentally. We then carry out numerical simulations with the same initial settings as experiments and analyze the flow line, velocity field, as well as the sweeping velocity of the bubbles. Comparisons also have been done among results obtained from theoretical calculations, numerical simulations, and experiments. Results indicate that the sweeping velocity increases with the increase in the bubble volume. In addition, the diameter of the pipeline significantly affects the moving tendency of the air bubbles.